Síntese, análise estrutural e avaliação do potencial inibitório frente à enzima tirosinase por complexos de oxidovánadio(IV) e dioxidovanádio(V) derivados de hidrazidas aromáticas. - Fioravanço, Letícia Paiva (2021)
Ten ligands were synthesized through aldol condensation of salicylic aldehyde and pyridoxal hydrochloride (C1AS, C2AS, C3AS, C4AS, C5AS, C1P, C2P, C3P, C4P and C5P) with five primary amines from p-substituted aromatic hydrazides (OH , CH 3 , NO 2 , NH 2 , H). These ligands were complexed by vanadium compounds (vanadyl acetoacetate(IV) – VO(acac)2 and vanadium pentoxide(V) – V2O5) obtaining ten new complexes, which were characterized by the following techniques: infrared spectroscopy, spectroscopy of visible ultraviolet, X-ray diffraction in single crystal and cyclic voltammetry. In addition, cyclic voltammetry experiments were carried out to observe the presence of redox processes and tests to quantify the inhibitory potential of the tyrosinase enzyme of ligands and complexes. Cyclic voltammetry results show a direct relationship between redox potentials and the inhibitory activity of the tyrosinase enzyme. While the C1AS complex had the lowest peak reduction current and the best inhibitory activity, the C1P complex had the highest peak reoxidation current and no inhibitory activity. Their respective ligands had activity contrary to them. Thus, it can be suggested that the metallic center of C1AS is responsible for the inhibitory activity of the complex, whereas in C1P the vanadium ion does not favor this activity, since the ligand alone is the one with the best activity.